Genetic correlation and mendelian randomization reveal the impact of sleep traits on urolithiasis risk - Mo Yan; Zhe-xin Zhang; Jia-xin Hu; Kai-bin Wang; Cheng-yi Liu (Scientific Reports)
Abstract Urolithiasis is a common and recurrent condition in the urological spectrum. Despite various proposed mechanisms, the causal relationship between sleep traits and the risk of urolithiasis remains unclear. We used publicly available genome-wide association study (GWAS) summary data from the UK Biobank and FinnGen to perform a two-sample Mendelian randomization (MR) analysis and genetic correlation analysis, evaluating the causal relationship and genetic correlation between sleep traits (chronotype, getting up in the morning, sleep duration, nap during the day, and insomnia) and urolithiasis (calculus of the kidney and ureter, and calculus of the lower urinary tract). Additionally, multivariable MR (MVMR) analysis adjusted for body mass index (BMI) and other sleep characteristics was conducted to assess the direct impact of sleep traits on the risk of urinary tract stones. The LD score regression (LDSC) analysis indicated a genetic correlation between insomnia and upper urinary tract stones (rg = 0.082, P = 0.017, Adjusted P = 0.085), but no significant genetic correlation was found for other sleep traits. Our results indicated no causal relationship between sleep traits and upper urinary tract stones. However, insomnia was significantly associated with a higher risk of lower urinary tract stones (IVW [inverse variance weighted] OR [odds ratio] = 5.91, 95% CI [confidence interval] 1.52–22.98, P = 0.010, Adjusted P = 0.030), while early rising exhibited a protective effect (IVW OR = 0.29, 95% CI 0.11–0.76, P = 0.012, Adjusted P = 0.030). In the MVMR analysis, insomnia consistently showed a similar trend, whereas daytime napping significantly reduced the risk of lower urinary tract stones (OR = 0.28, 95% CI 0.12–0.65, P = 0.003). This study provides MR-based evidence suggesting that insomnia may increase the risk of lower urinary tract stones, while daytime napping may reduce this risk. No causal relationship was found between sleep characteristics and upper urinary tract stones.